Factors Affecting Employee Job Satisfaction in the Kerinci Regent’s Office Case Studi: Employees of the Kerinci Regency Regional Secretariat Office - Jumia pestri; Rice Haryati; Novi Yanti (Fakultas Ekonomi, Universitas Ekasakti, 2025)
This study aims to determine the factors of work environment and work motivation on job satisfaction of employees of the Regional Secretariat of Kerinci Regency. The data collection techniques used are observation, interviews, and questionnaires. The type of data is qualitative data that is quantified with primary data sources. The population used in this study were 72 employees of the Regional Secretariat of Kerinci Regency using Total Sampling, the number of samples in this study were 72 employees. The data analysis method in this study uses multiple linear regression analysis, the coefficient of determination (R2) and hypothesis testing t test and F test. The results of this research show that: (1) The dominant indicator in the work environment variable is co-worker relationships at the same level as the TCR of 86.78%. The dominant indicator in the motivation variable is job security with a TCR of 87.67%. The dominant indicator of the job satisfaction variable is Wages with a TCR of 86.67%. (2) Work Environment has a positive and significant effect on Job Satisfaction of Kerinci Regency Regional Secretariat Employees (3) Work Motivation has a positive and significant effect on Job Satisfaction of Kerinci Regency Regional Secretariat Employees (4) Work Environment (X1) and Work Motivation (X2) together or simultaneously have a positive and significant effect on Job Satisfaction of Kerinci Regency Regional Secretariat Employees by 78.6%. Meanwhile, the remaining 21.4% was influenced by other variables outside this research.